The Influence Of Learning Media, Facilities, and Learning Interest on Students Motivation and Economic Learning Outcome At SMA Negeri District Tenayan Raya - Maharani, Mira; Gusnardi, Gusnardi; Gimin, Gimin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The method used in this research is quantitative to find out how the relationship between the media used by teachers, facilities, and students' interest in learning with motivation and learning outcomes in economics learning. The data obtained from this study are primary and secondary data. The total population in this study was 423 people with a total sample of 191 students of class X IPS at SMA Negeri 10 Pekanbaru, SMA Negeri 11 Pekanbaru and SMA Negeri 6 Pekanbaru. From the results of the research conducted, it can be seen that Learning Media has a positive relationship to Learning Motivation with a sig value of 0.000 <0.05, Facilities have a positive relationship to Learning Motivation with a Sig value of 0.000 <0.05. Learning interest does not have a positive relationship with learning motivation with a Sig value of 0.198 > 0.05. Learning Media does not have a positive relationship with Learning Outcomes with a Sig value of 0.132 > 0.05. Learning facilities do not have a positive relationship with learning outcomes with a Sig value of 0.783 > 0.05. Interest in learning has a positive relationship to learning outcomes with a Sig value of 0.048 <0.05. Learning Motivation has a positive relationship to Learning Outcomes with a Sig value of 0.047 <0.05. Learning Media has a positive relationship to Ask to Learn with a Sig value of 0.000 <0.05 and Learning Facilities do not have a positive relationship to Learning Outcomes with a Sig value of 0.152 > 0.05.